Media Sebagai Saluran Dakwah Lembaga Sosial Dan Komersial - Suriati; Said Ramadhan (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2020)
Media is everything, whether in the form of objects, humans, the results of mobile or immovable technology that can be used to transmit messages from the sender to the recipient, so as to stimulate thoughts, feelings, attention, and interests and attention of audiences in such a way that the information processing process occurs. . Then da'wah is a noble activity for every Muslim to do amar ma'ruf nahi munkar, so that the ultimate goal of da'wah is created, namely forming the khairul ummah. Furthermore, a social institution is a stable, stable, structured and well-established format in society that carries out activities based on the position of each individual or group, in an organized or orderly system of social relations that shows the existence of values, norms, regulations. , and the ways of relating to one another, which are arranged together to meet human needs in a given society. whereas commercial can be understood as an activity carried out for profit, either directly or indirectly.